TOURISM POLICY: POTENTIAL INCREASE OF ORIGINAL LOCAL INCOME - Mila Karmila; Ikeu Kania (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
Garut Regency called "Swiss van Java" has very beautiful natural scenery. This rich natural resource potency has not been the largest contributor to local original income. The poor implementation of tourism policy, particularly in exploring, inventorying, and developing tourist objects existing as the main attraction to tourists is one of its causal factor. The objective of research was to find out the effect of tourism policy implementation to local original income in Garut Regency. The research method employed was quantitative one; data collection was carried out by distributing questionnaire to 130 respondents. The data collected was then analyzed using simple regression data analysis with SPSS 23 help. The result of research showed that the implementation of tourism policy measured using standard and target, resource, inter-organization communication, executing organization characteristic, executiveâ€™s attitude, and social, economic, and political environment dimensions contributed to local original income by 38%.Â